Stabilitas Ukuran dan Sifat Optik Nanopartikel ZnO yang Dilapisi Polimer Tween 80 - Mirthelia Endah Oywari; Donn Richard Ricky; Horasdia Saragih (Journal of Pharmaceutical and Sciences, 2026)
Background: ZnO nanoparticles are widely used as UV filters in sunscreens due to their broad-spectrum protection and aesthetic transparency. However, agglomeration caused by high surface energy often compromises their efficacy. Coating with non-ionic polymers such as Tween 80 represents a potential stabilization strategy. Objective: This study aims to investigate the effect of varying Tween 80 concentrations on the size stability and optical properties of ZnO nanoparticles. Methods: Tween 80-coated ZnO nanoparticles were synthesized via a solvolysis method assisted by a rotor-stator homogenizer at Tween 80 volume variations of 1, 2, 3, and 4 mL in 50 mL of ethanol. Characterization was performed using a Particle Size Analyzer (PSA) and a UV-Vis spectrophotometer at day 0 and day 60. Results: Increasing Tween 80 concentration significantly reduced the mean diameter of nanoparticles from 17.9 nm to 11.4 nm and narrowed the size distribution (standard deviation decreased from 13.2 nm to 2.8 nm). The zeta potential remained near zero (-0.1 to -0.2 mV) due to the non-ionic nature of Tween 80, yet colloidal stability was maintained through a steric hindrance mechanism. After 60 days of storage, the 4 mL Tween 80 concentration was the most effective in limiting size growth (only 2.6%), compared to 83.7% for the 1 mL concentration. All samples exhibited high transmittance (>87%) in the visible light spectrum while maintaining strong UV absorption. Conclusion: An optimal Tween 80 concentration (4 mL in 50 mL ethanol) is crucial for producing ZnO nanoparticles with long-term size stability and superior optical properties, making them promising for next-generation sunscreen cosmetic formulations.